A New Tool to Explore Children's Social Competencies: The Preschool Competition Questionnaire. (16th March 2013) - Paquette, Daniel; Gagnon, Marie-Noëlle; Bouchard, Luc; Bigras, Marc; Schneider, Barry H.
Abstract : This paper presents the validation of Preschool Competition Questionnaire (PCQ). The PCQ was completed by the childcare teachers of 780 French-speaking children between the ages of 36 and 71 months. The results of exploratory factor analysis suggest three dimensions involving neither physical nor relational aggression: other-referenced competition, task-oriented competition, and maintenance of dominance hierarchy. The three dimensions are positively correlated with dominance ratings and are linked to social adjustment. Girls are just as competitive as boys in the dimensions of other-referenced competition and dominance hierarchy maintenance. Task-oriented competition is relatively more important in older children and girls. Classification analysis reveals that the children who obtain the highest dominance ratings are the ones who employ a variety of competition strategies.